Kerja Bakti Dan Penghijauan Lingkungan Kampung Mawokauw Jaya - Hizkia Rikcanto; Natalia Reyne Lumentah; Aslim Aslim (STIE Jambatan Bulan, 2024)
Environmental cleanliness is a major factor for creating health. Mawokauw Jaya Village is a village that is one of the community service programs to carry out community service work and environmental greening. The purpose of this service is to create a healthy, clean and beautiful environment of Mawokauw Jaya Village through community service activities and environmental greening. This activity is important to provide awareness, understanding and responsibility to local residents that the importance of preserving and preserving the surrounding environment because it can provide comfort and avoid diseases caused by waste from the actions of residents around the village. The method used in community service is the Participatory Action Research (PAR) method which involves the active participation of community members or groups to play a role in planning, implementing and evaluating actions that are adopted for the problems faced. The results of this community service activity can provide understanding and awareness to local residents to preserve the environment